Personal and Social Deixis as A Political Campaign Strategy Used in Donald Trump’s Rally - Johan Tobias Kristiano (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2021)
The use of personal and social deixis often has a crucial role in political speeches. This study investigated how personal deixis was used as a strategy to get other people’s support in Donald Trump’s presidential campaign speech. The object of the study was Trump’s speech in his presidential rally on October 10, 2020, and the data were the personal and social deixis in the speech. The occurrences of deixis were counted to reveal the parties to whom Trump gave his attention, and an analysis of the words used was conducted to see Trump’s attitudes toward the parties addressed by the deixis. The study revealed that Trump used personal deixis more than social deixis. There were five big parties to which he gave his attention using the deixis: the audience, Trump himself, the USA and its people, his opponents, and his party and government. Using the deixis, Trump also showed a positive attitude to his side and a negative attitude to the opponents. His use of personal and social deixis was also used as a campaign strategy. The deixis created inclusiveness, positioned Trump in different roles, showed support from several American communities, and influenced the audience’s attitude toward Trump’s opponents.